Reduction of CO2 emissions via cross-sector integration of community and industrial energy systems - Li, Ruonan (My University, 2023)
Integrating energy across different sectors is an efficient solution for improving energy systems to meet energy demands with low CO2 emissions. Such integration includes combining the supply and demand of heating, cooling, and electricity by implementing appropriate equipment, as well as combining the energy systems of civic and industrial sectors. This thesis develops various optimization approaches to identify the optimal design and operation of distributed energy systems and the integration of energy systems across commercial, industrial, and transportation sectors, which minimize CO2 emissions and costs of the systems. Available equipment of the energy systems includes combined cooling, heating, and power system, absorption chiller, solar thermal collector, photovoltaic, boiler, electric chiller, battery, ground source heat pump, and air source heat pump. This thesis provides the following contributions to this area. (1) Identify optimal structures of distributed energy systems under different electric grid CO2 footprints. The work implements representative periods when formulating the energy system, which reduces computation time. (2) Differentiate heating demands of entities in the integrated system at different temperature levels to ensure feasible heat transfer. It removes the simplified assumptions in existing studies on the integrated energy system that assume all heating demands are at a uniform temperature. (3) Optimize production rates of plants instead of assuming steady industrial production rates. The switchable production rates lead to a further reduction in CO2 emissions of the integrated system. (4) Identify the environmental and economic benefits of the integrated operation under different electric grid CO2 footprints. It presents that integrated operation reduces more CO2 emissions when the electric grid has higher CO2 footprints. (5) Identify the optimal relative sizes of entities in the integrated system that maximize the CO2 emissions reduction benefits brought by the integrated system. (6) Prove the integrated system has lower CO2 emissions than individual energy systems both under deterministic and stochastic scenarios. Overall, the work in this thesis contributes to developing energy systems and integrated energy systems with the lowest possible CO2 emissions under various scenarios.
Keywords: CO2 emissions reduction; Optimal integration of energy systems; Energy integration of buildings and light industry; Distributed energy system